Implementation of a Recycling Plant as a strategy for reverse logistics, sustainable and economic (Research, Society and Development, 2026)
The final management of urban solid waste constitutes one of the primary contemporary environmental challenges, particularly in small municipalities regarding the final disposal of waste. Sanitary landfills present themselves as an initial solution for waste management; however, they have increasingly become sites of significant waste regarding tangible recyclable materials. This study aims to analyze the technical, economic, and environmental feasibility of establishing a recycling plant in the municipality of Braúnas, Minas Gerais, Brazil, as a strategy for reverse logistics and the circular economy. Based on municipal operational data, it was determined that the municipality sends approximately 32.4 tons of urban solid waste per month to a landfill located in an adjacent municipality, incurring  monthly costs of nearly R$ 18,000. In a global context, approximately 2 billion tons of solid waste are generated annually, yet only 14% are properly recycled. Currently, 40% of all domestic solid waste sent to landfills in Brazil is recyclable—a missed opportunity that could otherwise generate up to 1 million direct jobs. Within this context, the establishment of a recycling plant emerges as a well-founded solution for mitigating operational costs, fostering the reinsertion of materials into the production chain through reverse logistics, stimulating employment opportunities, and reducing the negative externalities associated with environmental and social impacts. Furthermore, the study proposes domestic food self-production—where waste is transformed into a resource—through the integration of "Home Gardening and Composting," thereby enhancing food security and fostering a new vision for the future.